Determinants of corporate cash holdings in times of crisis: Insights from Brazilian sugarcane industry private firms - Manoel, Aviner Augusto Silva; Moraes, Marcelo Botelho da Costa; Santos, David Ferreira Lopes [UNESP]; Neves, Marcos Fava (Brill Academic Publishers, 2018)
The decision-making process regarding cash allocation, especially in times of recession, is somewhat challenging. Thus, the aim of this study is to evaluate the effects of the financial crisis in cash holdings of privately-held firms in the Brazilian sugarcane industry. For this purpose, a unique, hand-collected panel data of 31 firms for the period from 1998 to 2015 was used. The results show that the private firms of the industry maintain higher levels of cash than the average found by studies with Brazilian public companies. Furthermore, between the two dummy variables used, representing the subprime crisis and the most recent economic crisis in Brazil, only the second one was significant. Finally, in order to overcome the adverse conditions of the current Brazilian economic crisis, it was observed an increase in cash holdings, which, in turn, denotes the relevance of precautionary reasons in the understanding of cash management.
Keywords: Agri-food; Agribusiness; Cash management; Financial crisis; Treasury